(untitled) (Global Journal of Science Frontier Research, 2013)
The objective of this work was to select isolates of Trichoderma spp. with potential of antagonism against Sclerotina sclerotiorum, in vitro. We used ten isolates of Trichoderma spp. and an isolate of S.sclerotioruma long with "inhibition by Volatile Products" and "direct confrontation" techniques. The results of in vitro procedures, lead to the selection of the isolates JCOUFT-28, JCOUFT-37, JCOUFT-45, JCOUFT-63 and JCOUFT-85, which were Trichoderma spp. that showed better antagonistic activity on the isolated S.sclerotiorum.